Precedent within the high court - LAU, Kwan Ho (Institutional Knowledge at Singapore Management University, 2020)
A number of Masters and a Registrar have recently indicated that they, when exercising High Court jurisdiction, are not bound strictly to follow prior decisions made by Judges in the High Court. This represents a notable departure from the position established by and within the High Court, where since the Judicature Acts of 1873 and 1875 an unquestioning obeisance of the Master and Registrar towards such decisions has been generally expected and offered. Delving into questions of power, authority and jurisdiction, and examining relevant legislation such as the Civil Procedure Rules, this article constructs and analyses various arguments for and against recognising the co-equivalence of decisions of Judges, Masters and Registrars in the High Court.